Inferring the transmission intensity of malaria using genetic data - Hendry, JA (2020)
Despite a recent decline in prevalence, malaria still incurs a substantial burden on global health. Further progress towards elimination will require developing control strategies that are guided by detailed epidemiological surveillance. Yet, many existing surveillance approaches – including estimating parasite prevalence with community-level surveys, or tracking resistance with therapeutic efficacy studies -- are time consuming and labour intensive. There is an interest in harnessing the increasing availability of P. falciparum genetic data for surveillance, but several challenges remain outstanding. First, the relationships between genetic and epidemiological processes are poorly understood, hindering epidemiological inference from genetic data. Second, the ubiquity of mixed infections complicates analysis of malaria genetic data. Third, how the collection of genetic data can be efficiently integrated into malaria control is still being resolved.